The Effect of Career Planning and Development, Competence, and Human Resource Information System on Employee Performance at PtT Bank Negara Indonesia (Persero) Tbk - Illahiah, Dian Fajari; Mellita, Dina (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Human Resources (HR) in a company plays an important role because it is one of the success factors in the implementation of the company's activities. The industrial era 4.0 requires companies to be able to create high employee performance in company development. Without the support of reliable human resources (HR), the company's activities are not completed properly. This study aims to analyze 1) The Effect of Career Planning and Development, Competencies, and Human Resource Information Systems (HR) partially and simultaneously on employee performance at PT. Bank Negara Indonesia (Persero), Tbk., 2) The dominant variable that affects the performance of employees at PT. Bank Negara Indonesia (Persero), Tbk. This research uses quantitative methods, which are sourced from primary data through surveys of PT. Bank Negara Indonesia (Persero), Tbk. which in its calculations uses the SPSS (Statistical Package Social Sciences) program with data analysis techniques using Multiple Regression analysis. The research sample amounted to 96 employees of PT. Bank Negara Indonesia (Persero), Tbk. The results showed that 1) Career Planning and Development, Competence, and Human Resource Information System (HRIS) partially and simultaneously significantly affect the performance of employees at PT. Bank Negara Indonesia (Persero), Tbk. 2) Competency (X2) is the dominant factor that affects the performance of employees at PT. Bank Negara Indonesia (Persero), Tbk